MOBILITAS PENDUDUK MUSIMAN DI KOTA SURABAYA: Dampaknya Terhadap Lingkungan Permukiman Kumuh - Haning Romdiati; Mita Noveria (Research Centre for Population, Indonesian Institute of Sciences, 2008)
This article discusses temporary migrants and its impact on slums area in Surabaya. The influx of temporary migrants to Surabaya is more likely to be regarded as negative, instead of positive impacts. This is because tempora1y migrants mostly engage in the informal sector and live in slums and squatters. Most tempora1y migranrs come to Surabaya in search of work to improve their life. They tend to ignore the regulation of population administration (especially related to identity C(lrd oftemporwy population in the city, namely KIPEM) as well as settlement regulation (live in squatters). The influx of temporary migrcmts to slums and squatters is a reality that cannot be ignored To prohibit theft ow of temporary migrants coming to the city through 'close polic,y' is difficult to be established, because the policy opposed to human rights. Therefore, the policy needed is to give them a room the city. However, the city government has to implement the population and settlement regulation strictly and provide them with easily access to public facilities.Keyword: Population mobility, Temporary migrant, Slum and squatter, Population regristration